2007
DOI: 10.2337/dc06-1750
|View full text |Cite
|
Sign up to set email alerts
|

An Off-the-Shelf Instant Contact Casting Device for the Management of Diabetic Foot Ulcers

Abstract: OBJECTIVE—This study was designed to test the safety, effectiveness, and costs of off-loading with a novel, off-the-shelf irremovable device in the management of diabetic foot ulceration (DFU). RESEARCH DESIGN AND METHODS—We prospectively evaluated off-loading of neuropathic plantar ulcers in 40 diabetic outpatients attending our diabetic foot clinic and compared healing rates at the 12-week follow-up, number and severity of adverse events, healing time, costs and applicability of the device, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(123 citation statements)
references
References 25 publications
4
110
0
8
Order By: Relevance
“…Similar results were obtained in previous studies reported by Piaggesi et al (19) and Caravaggi et al (20); however, these two reports differ from our study in two important ways.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were obtained in previous studies reported by Piaggesi et al (19) and Caravaggi et al (20); however, these two reports differ from our study in two important ways.…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, below the knee removable walkers that have been made nonremovable may be as effective as TCCs and more effective than standard removable walkers in healing plantar foot ulcers. [47][48][49] Ulcer healing using removable devices is complicated by patients not adhering to recommendations for using The off-loading capacity of different modalities used for the prevention and treatment of diabetic plantar foot ulcers is expressed as percentage of peak pressure reduction at the first metatarsal head region compared with a control condition. The lighter bars show the range in measured peak pressure reduction over different studies.…”
Section: The Evidence Base: What Work and What Does Not Work?mentioning
confidence: 99%
“…The more complex a task is, in basic wound care, the less likely it will be carried out, properly or even not at all: applying a dressing in a minute is easy, but performing total contact casting (TCC) on a DFU can be challenging for a nonexpert, although instant TCC may ameliorate the problem to some extent. 28 Likewise, clinical practice guidelines-the cornerstone of wound care evaluation-still have a way to go so that clinicians can apply them with immediacy to their work. 29 Finally, inadequate reimbursement has consequences, as noted by Bolton et al: ''Sufficient evidence supports improved venous ulcer care in the U.S. but inadequate and/or inconsistent reimbursement policies impede quality evidence-based venous ulcer practice, delaying healing and increasing the burden of venous ulcers on society.''…”
Section: Why Should He Research Be An Important Factor In Reimbursemementioning
confidence: 99%